Entrance Skin Dose (Radiation) Measurement and Evaluation (for all age groups) at the State Specialist Hospital, Okitipupa, Nigeria - Ilori, Abiola Olawale; Ibitola, Gilbert; Ajanaku, Olanrewaju; Utomewore, Reuben Dapo (Open Science Journal, 2018)
This study was carried out on entrance skin dose (ESD) (Radiation) measurement and evaluation (for all age groups) at the State Specialist Hospital, Okitipupa, Ondo State, Nigeria. Entrance skin doses for randomly selected patients between 0-4 years, 5-9 years, 10-17 years and above 18 years old undergoing X-ray chest (Poster Anterior) examinations were measured and evaluation of the source-to-skin distance (SSD) records for the patients during the x-ray chest examinations were carried out. The mean ESD reported for chest PA projections were 66.43 µGy, 105.10 µGy, 215.76 µGy and 291.81 µGy respectively for age range 0 - 4 years, 5 - 9 years, 10 - 17 years and above 18 years. The ESD values reported in this present study were same with the NRPB recommendations of year 2000 of 50 µGy for newborn to 1-year-old, 70 µGy for 5 years and 120 µGy for 10 years old children. The values reported for age 1 to 4 years were lower than 0.1 mGy recommended and the mean ESD for age 5 to 9 years for chest PA examination was 0.11 mGy which is lower than the recommended 0.12 mGy. However, other values reported in this present study were compared with the guidance levels set by the International regulation bodies and were found to be within safe limits and they do not pose any significant health risk to the patients of all age ranges or the health workers. The effective radiation doses (ERDs) for all the age groups were computed, and by comparisons, it was found that the radiation risk factors (RRFs) are relatively low.